A Virological Study of Enterovirus Infections in Peninsular Malaysia - Samuel, Lihan; Saraswathy, T.S.; Zainah, Saat; Mohd Apandi, Yusof; Fauziah, Md Kasim; Tengku Rogayah, A.R.; R., Fazilah; A., Maizatul; Nor Shahidah, Khairullah (Elsevier Inc., 2022)
Background: Hand, foot, and mouth disease (HFMD) is a common illness in infants and children. It can be caused by many different human enteroviruses. Of these human enteroviruses, human enterovirus 71 (EV71) infection is more frequently associated with serious neurological complications and fatalities. The emergence of this virus emphasized the need for surveillance study and identification of EV71 to provide early warning of potential EV71 encephalitis outbreaks and assist in directing public health interventions as well as inform clinical decisions. This surveillance study was aimed to examine the prevalence of enteroviruses and EV71 in suspected clinical specimens. Methods: Samples preparation: Specimens with the clinical and epidemiological data were received from various hospitals in West Malaysia from January to December 2007. The samples were analyzed immediately upon arrival in our laboratory otherwise stored at −80 ◦C. RNA extraction: The RNA from the specimens were extracted using High Pure Viral Nucleic Acid Kit. PCR analysis and primer sequences: One step RT-PCR was employed with primers EVPCR1 (5-ACA-CGG-ACA-CCCAAA-GTA-GTC-GGT-TCC-3) and EVPCR2 (5-TCC-GGC-CCCTGA-ATG-CGG-CTA-ATC-C-3) for enteroviruses and MAS01S (5-ATA-ATA-GCA-YTR-GCG-GCA-GCC-CA-3) and MAS02A (5-AGA-GGG-AGR-TCT-ATC-TCY-CC-3) for EV71. Results: A total number of 2,381 clinical specimens were analyzed for the presence of enteroviruses and EV71 by RTPCR analysis. Out of all of the specimens analyzed, 531 (22.3%) were positive for enteroviruses and 21 (0.04%) of these were positive for EV71. These results showed that EV71 is less prevalent than other enteroviruses in the clinical specimens analyzed. Conclusion: The outcomes of the present surveillance study suggested that the EV71 which is more frequently associated with serious neurological and complications and fatalities is less prevalent than other enteroviruses. The results obtained also confirmed the usefulness of the PCR as a simple and rapid method for the detection of enteroviruses and discrimination of EV71 from other enteroviruses in clinical specimens.